New Powers of the National Director of the Internal Revenue Service (GESTIÓN Y TENDENCIAS, 2020)
In this article we analyze two of the new powers granted by Law 21,210 of 2020 to the National Director of the Internal Revenue Service, both relating to greater legal certainty and tax security. These are: a) the power to answer queries from private parties on the application of specific rules; and b) the Director's power to rule on hierarchical appeals against a decision rejecting a voluntary administrative review, with particular attention to the situation prevailing before this law was enacted. We close with some conclusions on these new powers.